2019
DOI: 10.2147/ijn.s220202
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chitosan And N, N, N-Trimethyl Chitosan Nanoparticle Encapsulation Of <em>Ocimum Gratissimum</em> Essential Oil: Optimised Synthesis, In Vitro Release And Bioactivity</p>

Abstract: Background: The encapsulation of plant essential oils (EOs) with polymeric materials (e.g. chitosan (CS) and N, N, N-trimethyl chitosan (TMC)) and the further reduction of the polymers into their nano sizes are gaining research interest in nanotechnology due to potential applications in medical drug delivery systems as well as the food and pharmaceutical industry. The present study reports a novel approach for the synthesis of Ocimum gratissimum essential oil (OGEO)-loaded CS and TMC nanoparticles with distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…For the cancer cells treated with OGM-40, membrane blebs were also observed after 48 h of incubation. This is an indication of cell apoptosis, as suggested by Onyebuchi and Kavaz 7 . The high antiproliferative activity of OGM-40 compared to the rest of the extracts is likely a result of oxidative stress generation within the cell membrane.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…For the cancer cells treated with OGM-40, membrane blebs were also observed after 48 h of incubation. This is an indication of cell apoptosis, as suggested by Onyebuchi and Kavaz 7 . The high antiproliferative activity of OGM-40 compared to the rest of the extracts is likely a result of oxidative stress generation within the cell membrane.…”
Section: Resultssupporting
confidence: 52%
“…Moreover, a study by Shahidi and Zhong 6 demonstrated the link between oxidative stress and the pathophysiology of several health conditions. Ocimum gratissimum L. often called clove basil or scent leaf, is indigenous to coastal, savannah, and tropical areas 7 , and is mostly found in tropical areas such as West Africa, Asia, Brazil, and India 8 . Ethnomedicinal applications have been reported for the plant due to its flowers and leaves being rich in polyphenols and other bioactive compounds 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Table 6 shows studies in which the antioxidant effects of EOs and their components have been analyzed using cell-free assays or melanoma models. Artemisia argyi -DPPH, ABTS, metal-ion chelation [28] Atriplex undulata -Crocin bleaching inhibition, DPPH [29] Cinnamomum cassia Cinnamaldehyde B16 [32] Chrysanthemum boreale Makino -DPPH, ABTS [31] Cryptomeria japonica -B16 [220] Cuminum Cyminum -DPPH, superoxide anion radical-scavenging activity, β-carotene/linoleic acid [35] Curcuma aromatica -DPPH [36] Curcuma kwangsiensis -DPPH [37] Dalbergia pinnata -DPPH, ABTS [39] Eucalyptus camaldulensis -DPPH, ABTS, B16-F10 [41] Eugenia uniflora -DPPH, β-carotene/linoleic acid [43] Glechoma hederacea β-carotene/linoleic acid, B16 [44] Helichrysum microphyllum -DPPH, ABTS [45] Hypericum hircinum -DPPH, ABTS [47] Lavandula augustifolia -B16-F10 [49] Melaleuca quinquenervia 1,8-Cineole, α-pipene, α-terpineol B16 [53] Ocimum basilicum -DPPH, hypoxanthine/xanthine oxidase [58] Ocimum gratissimum -DPPH, hypoxanthine/xanthine oxidase [58,237] Ocimum micranthum -DPPH, hypoxanthine/xanthine oxidase [58] Ocimum tenuiflorum -DPPH, hypoxanthine/xanthine oxidase [58] Table 6. Cont.…”
Section: Chemopreventive Activitymentioning
confidence: 99%
“…Mesoporous silica nanoparticle Antibacterial [7] Pepper VOCs Mesoporous silica nanoparticle Antibacterial [113] Coleus aromaticus VOCs Silver nanoparticle Antibacterial [168] Eugenia caryophyllata VOCs Chitosan nanoparticle Antifungal [143] Carvacrol Nanoemulsion Antifungal [169] Zataria multiflora VOCs Solid lipid nanoparticle Antifungal [146] Cymbopogon citratus VOCs Poly (D,L-lactide-co-glycolide) nanoparticles Antiviral [148] Artemisia arborescens VOCs Nanoliposome Antiviral [149] Santolina insularis VOCs Nanoliposome Antiviral [150] Curcuma longa & Cymbopogon citratus VOCs Chitosan-alginate nanocapsule Anticancer [151] Ocimum Gratissimum VOCs Chitosan nanoparticle Trimethyl chitosan nanoparticle Anticancer [152] Citral Bovine serum albumin nanoparticle Anticancer [154] Citrus bergamia VOCs Nanoliposome Anticancer [155] Ginger & frankincense VOCs Nanoemulsion Anticancer [157] Origanum glandulosum VOCs Sodium alginate nanocapsule, nanoemulsion Anticancer [158] Mentha spicata VOCs Nanoemulsion Anticancer [170] Citral Solid lipid nanoparticle Anticancer [171] Nigella sativa VOCs Gold nanoparticle Anticancer, antibacterial [117] fection of catfish with a very low concentration (5 µL/L) of volatiles is more environmentally safe and cost-effective [137]. The antibiofilm effects of free cinnamon oil and nanoliposomes carrying the oil were tested against MRSA by Cui et al The logarithmic value of a viable MRSA population in the biofilms treated with cinnamon oil was decreased by 1.49 times whereas those treated with cinnamon oil-loaded nanoliposomes led to the reduction of MRSA cells by 2.45 times.…”
Section: Solid Lipid Nanoparticle Nanostructured Lipid Carriermentioning
confidence: 99%
“…Trimethyl Ch-NPs carrying Ocimum gratissimum VOCs, and free volatile compounds, were tested for impact on cell viability and antiproliferation of breast cancer (MDA-MB-231) cells. After 48 h incubation, the viability of MDA-MB-231 cells was reduced to approximately 40 % in response to treatment of 50 µg/mL of volatile-laden Ch-NPs, which exhibited more cytotox-icity against cancer cells than free volatiles, causing about 70 % cell viability at the same concentration [152]. It is thought that the Ch-NPs could penetrate the cancer cell membranes and cause DNA damage, leading to defects in the cellular genes [153].…”
Section: Anticancer Activitymentioning
confidence: 99%